Effect of tropical climates on the quality of commonly used antibiotics: the protocol for a systematic review and meta-analysis - Johnstone Thitiri; Moses Ngari; Christina W Obiero; James A Berkley; Tsegaye Melaku; Sultan Suleman; Gemmechu Hasen; Sileshi Belew; Jimmy Shangala (BMJ Open)
Introduction Medicine quality can be influenced by environmental factors. In low- and middle-income countries (LMICs) with tropical climates, storage facilities of medicines in healthcare settings and homes may be suboptimal. However, knowledge of the effects of temperature and other climatic and environmental factors on the quality of medicines is limited. A better understanding of the effects of climates may assist in the development of control strategies to help reduce factors contributing to poor-quality medicines. Therefore, this systematic review aims to synthesise data from published studies describing the effects of storage conditions on the quality of antibiotic medicines commonly used in LMICs.Methods and analysis We will search literature from databases, including the PubMed, Web of Science, Scopus and Google Scholar, and grey literature between 1987 and 2022. Experimental studies that evaluate the influence of temperature, humidity and sunlight on the quality of antibiotics applicable to Africa and South Asia will be included. Experimental studies that assess naturally occurring and simulated storage conditions and medicines prepared from powder with water and stored in hospitals or at home to be used across several doses will be also included. The key search terms related to the tropical climate, quality and commonly used antibiotics, such as temperature, storage condition, humidity, sunlight and moisture; quality, assay, purity, dissolution, disintegration, hardness, friability, weight variation, weight uniformity, degradation, impurities and stability; and amoxicillin, ceftriaxone, azithromycin, ciprofloxacin, doxycycline, metronidazole, trimethoprim-sulfamethoxazole, erythromycin, ampicillin and gentamicin, respectively, will be connected using the appropriate Boolean operators (OR, AND). The search terms will be used in correspondence with Medical Subject Heading terms by keyword arrangement. The available evidence for the poor quality of commonly used antibiotics is summarised by the type of diagnosis, type of drug and region. Meta-analysis using random effects will be performed using RevMan software to determine the pooled effects of environmental exposures. The degree of heterogeneity will be evaluated by the inverse of variance (I2). Forest plots will be used to present the meta-analysis data.Ethics and dissemination Ethical approval is not required as the study is a systematic review. This review will be disseminated through open-access peer-reviewed publication.PROSPERO registration number CRD42023432848.